IbM KELOMPOK TANI WANITA DI PARANGLOE - Saida, Saida (Jurnal BALIRESO, 2019)
The problems faced by the Nusa Indah Women's Farmers Group are limited water sources forwatering and do not yet know how to quality vegetable seeds, while the Women Melati Farmersgroup the problem is not knowing the spatial layout of the land and not knowing the making oforganic fertilizers from household waste. This activity aims to provide knowledge and skills forNusa Indah and Melati farmer groups to streamline the use of water for watering, use of qualityseeds, making organic fertilizers from household waste, and structuring spatial land. The methodused in the Science and Technology Program for the Community is counseling, productiontraining, and mentoring. Expected outputs are bokashi fertilizer products, appropriate technology,and scientific publications. The results of the service activities are (1) the material provided in theextension and training activities is knowledge and skills to overcome the problem of managinghousehold waste into compost and the use of land for vegetable cultivation. (2) Farmersparticipating in the counseling and training apply the knowledge and skills obtained in theactivities of managing household waste into compost and the use of land for vegetable cultivation.The application of knowledge and skills increases the productivity of the yard planted withvegetables. (3) This service activity received a positive response from the participants and hopedthat such activities would be sustainable.